Evaluation of anticoagulation and nonsurgical major bleeding in recipients of continuous‐flow left ventricular assist devices - Veasey, Tara M.; Floroff, Catherine K.; Strout, Sara E.; McElray, Krista L.; Brisco‐Bacik, Meredith A.; Cook, Jennifer L.; Toole, John M.; Craig, Michael L.; Van Bakel, Adrian B.; Meadows, Holly B.; Uber, Walter E. (Artificial organs, 2019)
Continuous‐flow left ventricular assist device (LVAD) placement has become a standard of care in advanced heart failure treatment. Bleeding is the most frequently reported adverse event after LVAD implantation and may be increased by antithrombotic agents used for prevention of pump thrombosis. This retrospective cohort included 85 adult patients implanted with a Heartmate II LVAD. Major bleeding was defined as occurring >7 days after implant and included intracranial hemorrhage, events requiring 2 units of packed red blood cells within a 24‐h period, and death from bleeding. Primary outcome was intensity of anticoagulation between patients with or without at least one incidence of nonsurgical major bleeding. Major bleeding occurred in 35 (41%) patients with 0.48 events per patient year and a median (IQR) time to first bleed of 134.5 (39.3, 368.5) days. The median (IQR) INR at time of bleed was 1.7 (1.4, 2.5). Median INR during follow‐up did not differ between groups and patients with major bleeding were not more likely to have a supra‐therapeutic INR. Patients who bled were more likely to have received LVAD for destination therapy, to have lower weight, worse renal function, and lower hemoglobin at baseline. Duration of LVAD support and survival were similar between groups with no difference in occurrence of thrombosis. Incidence of nonsurgical major bleeding was not significantly associated with degree of anticoagulation. Certain baseline characteristics may be more important than anticoagulation intensity to identify patients at risk for bleeding after LVAD implant. Modification of anticoagulation alone is not a sufficient management strategy and early intervention may be required to mitigate bleeding impact.